AAGBS UiTM strengthens AI ecosystem through AI nusantara collaboration - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
AAGBS was invited to the DoubleTree by Hilton, I-City, Shah Alam to receive a certificate of appreciation from Al Nusantara by SELANGOR DIGITAL SCHOOL. This certificate is awarded to AAGBS in recognition of the school's commendable contribution and active participation in the Al Nusantara community, demonstrating a commitment to advancing knowledge and fostering collaboration in the field of artificial intelligence. The event was graced by YB Tuan Ng Sze Han, Selangor EXCO of Investment, Trade & Mobility and Dato' Syed Haizam Jamalullail, the Director of Al Nusantara. The award was received by the Dean of AAGBS, Professor Dr Syed Jamal Abdul Nasir Syed Mohamad. Several other Al Nusantara University Partners such as Unisel, Sunway University, Monash University, the University of Nottingham and Putra Business School were also present at the momentous occassion to receive similar award. The Al Nusantara program, spearheaded by Selangor Digital School (SDS), is a groundbreaking initiative designed to nurture talents in Artificial Intelligence (AI). SDS aims to create a dynamic learning ecosystem that empowers students with essential skills, ensuring the younger generation is well-prepared to embrace Al technology. Aligned with the educational vision of the Selangor state government, SDS, through the Al Nusantara program, contributes to the digital transformation, fostering entrepreneurship and the growth of unicorn-status companies in the digital economy sector. AAGBS UITM is delighted to be part of this initiative, recognizing its potential to shape the future. The faculty takes pride in the program's commitment to provide a valuable opportunity for students to benefit from real-world insights and expertise in the field.